Body Composition and Anthropometric Measures of Footballers, Cup Winners of Montenegro and Bosnia and Herzegovina - Dusko Bjelica; Jovan Gardasevic; Ivan Vasiljevic; Marin Corluka (Journal of Anthropology of Sport and Physical Education)
The aim of this research was to determine the diff erences among the top football players of the Montenegrin club FC Sutjeska-Niksic and Bosnia and Herzegovina club FC Siroki Brijeg, the Cup winners in their countries, in the anthropometric measures and body composition. A sample of 45 examinees is divided into two sub-samples. The fi rst sub-sample of the examinees consisted of 23 players of FC Sutjeska-Niksic of the average age of 21.69±4.30, the champions of the Cup of Montenegro in the season 2016/17, while the other sub-sample consisted of 22 players of FC Siroki Brijeg of the average age of 24.00±6.22, the champions of the Cup of Bosnia and Herzegovina in the season 2016/17. Football players were tested immediately after the end of the competition season 2016/17. Anthropometric measures in the body composition were evaluated by a battery of 10 variables: body height, body weight, waist size, triceps skin set, biceps skin set, back skin set, abdominal skin set, body mass index, fat percentage and muscle mass. The standard central and dispersive parameters of all variables are calculated. The signifi cance of the diff erences between the players of the top two football clubs in the anthropometric measures and variables for assessing body composition was determined by a t-test for independent samples. It was found that the football players of the two mentioned clubs don’t have statistically signifi cant diff erences by the variables.